Beneficiation of Coal from Bonehau, Mamuju Regency of West Sulawesi Province Using Column Flotation - William, Gabriel Wendiarto; Sufriadin, Sufriadin (Journal of Metallurgical Engineering and Processing Technology, 2024)
Coal is a heterogeneous substance with organic and inorganic and associated with a number of mineral matters that can reduce coal quality. Coal combustion will convert mineral matters into ash content that can affect furnace performance. Coal beneficiation is the process of improving coal quality with a number of methods to reduce ash content and increase coal calorific value. One of the coal beneficiation method is flotation which involves a solid phase in the form of coal particles, a liquid phase in the form of water, and a gas phase in the form of air bubbles as factors that affect the flotation process. This study aims to determine the coal quality, and to analyze the effect variables on ash content and calorific value. The methods used in this study were microscopic optical and X-Ray Diffraction (XRD) analysis for coal mineralogy and proximate analysis and calorific value analysis for coal quality. The column flotation method using flotation time, grain size, and collector dosage as research variables. The results of coal mineralogy analysis showed the coal sample contained of quartz, pyrite, moganite, and graphite with 5.07% of ash and 5,207 cal/g of calorific value. Results of the flotation experiment reveal that the lowest ash content were 2.83% which was found with the grain size of 60 mesh, a flotation time of 10 minutes, and 20 mL of collector dose. The highest calorific value analysis results were 5,835 cal/g which obtained at a grain size of 100 mesh, flotation time of 15 minutes, and a collector dose of 20 mL.